Hubungan Gaya Hidup Sehat Dengan Perilaku Kepedulian Sosial Pada Remaja - Nur Adila; Syazwina Dinda Damara Rais; Tri Fauziah Hasana; Usiono Usiono (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study discusses the relationship between healthy lifestyle and social care behavior in adolescents. A healthy lifestyle that includes a balanced diet, regular exercise, adequate sleep, and effective stress management, plays an important role in improving the physical and mental health of adolescents. Good mental health affects the increase in empathy and social interaction, which leads to an increase in social care behavior. Adolescents who live a healthy lifestyle tend to be more sensitive to social needs and more active in various social activities that support the welfare of others. Conversely, adolescents who do not adopt a healthy lifestyle tend to have difficulty managing emotions and social relationships. This study emphasizes the importance of promoting a healthy lifestyle among adolescents as an effort to create a healthy, caring, and active generation in building a more harmonious and supportive community.